Impacts of Climate Change in Nepalese Agriculture - Shrestha, Suman Kumar; Gurung, Gem Prasad (Nepalese Journal of Development and Rural Studies, 2018)
This paper presents impact of climate change in agriculture and adaptation strategies applying by the farmers. In doing so, secondary data and information as well as document review methods are applied. The study found that climate change has affected the different sectors such as agriculture and non-agriculture. Especially agriculture is the more affected than non- agricultural sector. The major crops production trend is gradually decreasing due to the negative impact of climate change. Comparatively, climate change has more affected in the Himalayas and hilly region than Tarai. Owing to that farmers are applying different adaptation strategies for minimizing the climate change impact on productions. However, federal governments must prepare and implement the attractive affirmative policies that are needed to motivate small farmers living in Mountain, Hill and Tarai region.